The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1186/s40510-022-00434-3
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative three-dimensional evaluation of maxillary basal and dentoalveolar dimensions in patients with and without maxillary impacted canines

Abstract: Background This study aimed to three-dimensionally evaluate the qualitative and quantitative maxillary basal, dentoalveolar, and dental dimensions in patients with unilateral or bilateral maxillary impacted canines relative to their normal peers. Materials and methods This is a retrospective comparative study. Cone-beam computed tomography images of one hundred and fifty adult patients were divided into three equal groups: unilateral, bilateral, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Investigation of activity of the craniomandibular system muscles is very important during the growth of a child, in a period of mixed bite. Functional disorders, particularly breathing, and swallowing functions, are found frequently in childhood and may cause a narrowing upper jaw [4,15,21,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of activity of the craniomandibular system muscles is very important during the growth of a child, in a period of mixed bite. Functional disorders, particularly breathing, and swallowing functions, are found frequently in childhood and may cause a narrowing upper jaw [4,15,21,25].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of posterior crossbite can include any combination of dental, skeletal, and neuromuscular functional components, but the most frequent cause is a reduction in the width of the maxillary dental arch. Such a reduction can be induced by bad habits or obstruction of the upper airways caused by adenoid tissues, allergic rhinitis, or septal deviation [2,15,21,26]. Previous studies have shown that posterior crossbite in children and adolescents has been associated with asymmetrical function and performance of the masticatory muscles [2].…”
Section: Introductionmentioning
confidence: 99%
“…stated that the maxillary rst molar basal bone widths were signi cantly reduced in patients with impacted maxillary canines. Recently, a CBCT assessment declared that, basal bone and alveolar widths of the maxillary rst premolars and molars were reduced in the unilateral and bilateral impacted maxillary canine groups than controls [35]. Conversely, Saiar et al [36], examined the posteroanterior cephalograms of patients with palatally impacted maxillary canines, and reported no association between the skeletal maxillary width and the impaction.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated using the G*power software (version 3.1.9; Franz Faul Universitat, Kiel, Germany). Power analysis before the study was calculated with reference to the intercanine width, as evaluated in the study by Sharhan et al [ 9 ]. According to the power analysis, the total sample size was determined to be 30, with a desired power (1-b) of 0.95 at the conventional a level (0.05) and an effect size of 0.77.…”
Section: Methodsmentioning
confidence: 99%